Enactment of a Geoscience Curriculum by Using Innovative Curriculum Materials–An Exploratory Case Study - Hansen, Henning; Hlawatsch, Sylke; Lücken, Markus (Journal of Geography Education, 2007)
Trying to implement interdisciplinary geo-science curriculum materials in geography and science education we asked how they fit into teachers’ existing practices, their needs for support and strategies to plan instruction. The focus of our case study has been the identification of the goals teachers pursue with the materials, of strategies for customizing and using them in the classroom and of the features of the local context that help to enact an interdisciplinary geoscience curriculum. The study made use of three independent data sources: the results of a workshop questionnaire, the written outcomes of enactment scenarios and the transcripts of telephone interviews. In section 1 the theoretical background is presented that includes ideas on lesson planning, the customization of curriculum materials and the relationship between implementation and local enactment. Section 2 describes the case study approach and section 3 the outcomes, starting with the goals teachers plan to pursue with the curriculum materials and the enactment strategies that indicate how they use the materials (3.1). Section 3.2 presents details on supportive and hindering conditions for local enactment and 3.3 selected data about the practical realization of the scenarios in the classroom. We found that the term "quarry" is a metaphor that allows describing the strategy of most practitioners to deal with innovative curriculum materials. Moreover, our study has shown the central role of modular curriculum materials for the implementation of geoscience education combined with opportunities to learn through well structured in-service workshops. Based on these outcomes, summary chapter 4 presents suggestions for a successful local enactment of geoscience curriculum materials.